2007
DOI: 10.1111/j.1365-2486.2007.01525.x
|View full text |Cite
|
Sign up to set email alerts
|

Voltinism flexibility of a riverine dragonfly along thermal gradients

Abstract: Potential effects of future warming should be reflected in life history patterns of aquatic organisms observed in warmer climates or in habitats that are different in ambient temperature. In the special case of the dragonfly Gomphus vulgatissimus (L.) (Odonata: Gomphidae) previous research suggests that voltinism decreases from south to north. We analysed data on voltinism from 11 sample sites along a latitudinal gradient from about 441N to 531N, comprising small streams to medium-sized rivers. Furthermore, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 33 publications
3
74
0
Order By: Relevance
“…Biogeographic studies within the AQUASHIFT consortium were focussed on dragonflies, snails, and ciliates. The dragonfly studies showed both direct range shifts as well as latitudinal shifts of life cycles, for example, in voltinism, which likely cause range shifts (Braune et al 2008;Flenner et al 2010;Söndgerath et al 2012). A modeling study on the distribution of NW European freshwater pulmonate snails (Burgmer et al 2007;Cordellier et al 2012;Pfenninger et al 2011) predicted range shifts based on present-day temperature niches of snails.…”
Section: Range Shiftsmentioning
confidence: 99%
“…Biogeographic studies within the AQUASHIFT consortium were focussed on dragonflies, snails, and ciliates. The dragonfly studies showed both direct range shifts as well as latitudinal shifts of life cycles, for example, in voltinism, which likely cause range shifts (Braune et al 2008;Flenner et al 2010;Söndgerath et al 2012). A modeling study on the distribution of NW European freshwater pulmonate snails (Burgmer et al 2007;Cordellier et al 2012;Pfenninger et al 2011) predicted range shifts based on present-day temperature niches of snails.…”
Section: Range Shiftsmentioning
confidence: 99%
“…Also, an interaction between voltinism and the extension of a species' range-limits are predicted (Crozier & Dwyer 2006). A longer flight period caused by warmer temperatures may induce changes in phenology (Braune et al 2008) and allow production of an increased number of generations per season (Roff 1980;Yamamura & Kiritani 1998;Braune et al 2008). In partially bi-or multi-voltine species an increase in individuals belonging to the second or subsequent generations is expected (Roff 1980;Stearns 1992), since a larger proportion of the first generation's offspring will directly develop and reproduce within the same season, rather than diapause.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a 2-year life cycle was predicted for this species up to N50°, based on modeling population dynamic along a latitudinal gradient (Braune et al, 2008). In our study the Rivers Tisza and Szamos met these criteria.…”
Section: Discussionmentioning
confidence: 83%
“…The voltinism of Odonata is relatively flexible, depending on photoperiod and water temperature in temperate regions (Braune et al, 2008;Corbet et al, 2006). At our sampling sites life cycles 2 to 3 years long are suggested for both studied species Söndgerath et al 2012).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation